2020
DOI: 10.1017/jog.2020.86
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic strengthening of lake ice

Abstract: Further to systematic experiments on the flexural strength of laboratory-grown, fresh water ice loaded cyclically, this paper describes results from new experiments of the same kind on lake ice harvested in Svalbard. The experiments were conducted at −12 °C, 0.1 Hz frequency and outer-fiber stress in the range from ~ 0.1 to ~ 0.7 MPa. The results suggest that the flexural strength increases linearly with stress amplitude, similar to the behavior of laboratory-grown ice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Acoustic emission hit rate during cycling increases with an increase of stress amplitude of cycling. Flexural strength of saline ice of 3.0±0.9 ‰ salinity appears to increase linearly with increasing stress amplitude, similar to the behavior of laboratory-grown freshwater ice (Murdza et al, 2020c) and to the behavior of lake ice (Murdza et al, 2020a). The flexural strength of saline ice of 5.9±0.6 ‰ depends on the vertical location of the sample within the thickness of an ice puck; i.e., the strength of the upper layers, which have a lower brine content, was found to be as high as three times that of lower layers.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Acoustic emission hit rate during cycling increases with an increase of stress amplitude of cycling. Flexural strength of saline ice of 3.0±0.9 ‰ salinity appears to increase linearly with increasing stress amplitude, similar to the behavior of laboratory-grown freshwater ice (Murdza et al, 2020c) and to the behavior of lake ice (Murdza et al, 2020a). The flexural strength of saline ice of 5.9±0.6 ‰ depends on the vertical location of the sample within the thickness of an ice puck; i.e., the strength of the upper layers, which have a lower brine content, was found to be as high as three times that of lower layers.…”
supporting
confidence: 57%
“…Figure 8 shows measurements obtained from saline ice of both salinities cycled at -10 º C at an outer-fiber displacement rate of 0.1 mm s -1 . For comparison, data from laboratory grown freshwater ice (Murdza et al, 2020c) of S2 character and from lake ice of the same character (Murdza et al, 2020a) are also shown. The relationship between the flexural strength, and cycled stress amplitude, , for saline ice appears to be a linear one and, within experimental scatter, to have essentially the same sensitivity to stress amplitude as freshwater ice; namely:…”
Section: Flexural Strength Versus Stress Amplitudementioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic emission hit rate during cycling increases with an increase in stress amplitude of cycling. Flexural strength of saline ice of 3.0 ± 0.9 ‰ salinity appears to increase linearly with increasing stress amplitude, similar to the behavior of laboratory-grown freshwater ice (Murdza et al, 2020b) and to the behavior of lake ice (Murdza et al, 2021). The flexural strength of saline ice of 5.9 ± 0.6 ‰ depends on the vertical location of the sample within the thickness of an ice puck; i.e., the strength of the upper layers, which have a lower brine content, was found to be as high as 3 times that of lower layers.…”
supporting
confidence: 57%
“…Cyclic loading may also play an important role in other scenarios. For instance, during ice-structure interactions (Jordaan, 2001;Hendrikse and Metrikine, 2016;O'Rourke et al, 2016;Jordaan et al, 2008) the structure itself, such as a lighthouse, may be weakened or damaged to a degree that depends on the strength of the ice. Other examples are runways and roads that are built by freezing water on cold oceans, rivers, and lakes and subsequently subject to cyclic loading.…”
Section: Introductionmentioning
confidence: 99%